Comparison between mitochondrial DNA sequences in low grade astrocytomas and corresponding blood samples. Issue 3 (1st June 2002) - Kirches, E; Krause, G; Weis, S; Mawrin, C; Dietzmann, K
Abstract : Background/Aims: To identify somatic mutations in the mitochondrial DNA of glioblastomas, in a previous study the displacement loops of 17 glioblastomas and corresponding blood samples were sequenced and instabilities in repeats or transitions were detected in seven tumours. This study was extended by sequencing 10 DNA samples of diffuse astrocytomas (World Health Organisation grade II) and corresponding blood samples. Methods: The 10 DNA samples of diffuse astrocytomas and corresponding blood samples were amplified and sequenced using fluorescent nucleotides. Results: No sequence differences were detected, with the exception of a quantitative shift between two genotypes heteroplasmic within the hypervariable region 2, which can be interpreted as mitotic drift. In the glioblastoma series, any particular somatic mutation was usually found in only one tumour. The only frequent alteration was coupled to a mitochondrial germline polymorphism under-represented in the low grade astrocytoma group. Moreover, a single mutation in two patients with secondary glioblastomas had already been detected in diffuse astrocytomas of these individuals. Conclusions: A lower percentage of mitochondrial DNA mutations in low grade tumours cannot be deduced from these data.